Digital leadership and safety management: Maximizing safety performance through employee competence - Utik Bidayati (Universitas Ahmad Dahlan, 2026)
Purpose-This study examines the mediating role of employee competence in the relationship between digital leadership, safety management, and safety performance in hospitals in Surabaya, Indonesia. In the era of digital transformation, hospitals must enhance patient and staff safety through digitally competent leadership and structured safety management systems. Methodology-A quantitative, multi-site cross-sectional design was applied in several hospitals in Surabaya, involving 161 healthcare workers who had worked for at least one year and were involved in safety-related decision making. Data were collected via an online questionnaire using a 1–5 Likert scale and analyzed with SmartPLS 4.0. Findings-The results show that safety management, digital leadership, and employee competence have positive and significant effects on safety performance, with employee competence mediating the impacts of digital leadership and safety management. These findings highlight safety management as a foundational capability, while digital leadership and employee competence act as complementary drivers of safety performance. Research Limitations-This study is limited to healthcare workers from several hospitals in Surabaya using a cross-sectional design, so generalizations to other regions and causal inferences should be made with caution. The reliance on perceptual data also has the potential to introduce subjective bias. Novelty-The study introduces and empirically tests the Digital–Safety–Competence Triad by integrating the Natural Resource-Based View and the Ability–Motivation–Opportunity framework in Indonesian hospitals, and offers practical guidance for hospital management to institutionalize digital safety monitoring, competence-based training, and systematic evaluation of safety performance.